Asymmetric electron angular distributions in resonant dissociative photoionization of H2 with ultrashort xuv pulses (2009)
ABSTRACT: Photoelectron angular distributions from fixed-in-space H2 molecules exposed to ultrashort xuv laser pulses have been evaluated. The theoretical method is based on the solution of the time-dependent Schrödinger equation in a basis of stationary states that include all electronic and vibrational degrees of freedom. Asymmetric angular distributions are observed as a consequence of the delayed ionization from the H2 doubly excited states, which induces interferences between gerade and ungerade ionization channels. The analysis of this asymmetry as a function of pulse duration can provide an estimate of the corresponding autoionization widths.